Experimental toxicity study of orally ingested detoxified Manashila (realgar) treated in liquid herbal and animal drugs - Madhuri S Pawar; Deepali Suryawanshi; Priti Dhande (Wolters Kluwer Medknow Publications, 2023)
Introduction: Manashila (reaglar) is one of the arsenicals used in traditional ayurvedic treatments to treat various respiratory, neurological, and skin manifestations. However, the toxicities of realgar are well documented; thus, there is an increased fear to use ayurvedic formulations which contain this type of arsenic in treatment. On the other hand, in ayurvedic pharmaceutics, specific processes are recommended to nullify the untoward effects of Manashila, before it is used in formulations. Thus, to generate the toxicity profile of two samples of Manashila processed in the juice of Eclipta alba and a mixture of juice plus goat urine (GU), a subacute toxicity study was undertaken. Methods: As per the standard guidelines, the raw form of Manashila was boiled in the juice of E. alba and a mixture of the juice of E. alba plus GU for 12 h, and two samples of detoxified Manashila were prepared. Those samples were then tested in animals against the control group. Drugs were administered in a limited drug dose (1000 mg/kg) to animals for 28 days. Hematological, biochemical, and histopathological studies of all three groups were compared statistically. Results: Two samples of detoxified Manashila exhibited an almost nontoxicological profile as those samples did not show any significant toxicity signs in animals. Some of the biochemical values were altered; however, those were not significantly different than control group. Conclusion: It can be concluded that two samples of detoxified Manashila did not produce any significant toxic effects at 1000 mg/kg dose and are relatively safe.